Therapeutic Benefit of Extended Thymosin β4 Treatment Is Independent of Blood Glucose Level in Mice with Diabetic Peripheral Neuropathy - Lei Wang; Michael Chopp; Longfei Jia; Xuerong Lu; Alexandra Szalad; Yi Zhang; RuiLan Zhang; Zheng Gang Zhang (Journal of Diabetes Research)
Peripheral neuropathy is a chronic complication of diabetes mellitus. To investigated the efficacy and safety of the extended treatment of diabetic peripheral neuropathy with thymosin β4 (Tβ4), male diabetic mice (db/db) at the age of 24 weeks were treated with Tβ4 or saline for 16 consecutive weeks. Treatment of diabetic mice with Tβ4 significantly improved motor (MCV) and sensory (SCV) conduction velocity in the sciatic nerve and the thermal and mechanical latency. However, Tβ4 treatment did not significantly alter blood glucose levels. Treatment with Tβ4 significantly increased intraepidermal nerve fiber density. Furthermore, Tβ4 counteracted the diabetes-induced axon diameter and myelin thickness reductions and the g-ratio increase in sciatic nerve. In vitro, compared with dorsal root ganglia (DRG) neurons derived from nondiabetic mice, DRG neurons derived from diabetic mice exhibited significantly decreased neurite outgrowth, whereas Tβ4 promoted neurite growth in these diabetic DRG neurons. Blockage of the Ang1/Tie2 signaling pathway with a neutralized antibody against Tie2 abolished Tβ4-increased neurite outgrowth. Our data demonstrate that extended Tβ4 treatment ameliorates diabetic-induced axonal degeneration and demyelination, which likely contribute to therapeutic effect of Tβ4 on diabetic neuropathy. The Ang1/Tie2 pathway may mediate Tβ4-induced axonal remodeling.